Diseño arquitectónico de un mercado municipal en la comuna Monteverde - Escudero Vélez, Joyce Isabel (2024)
The present endeavor aims to undertake the architectural design of a Municipal Market applying biomimicry in the Monteverde Commune. The central focus of the research is directed toward the integration of biomimetic concepts to achieve a design that harmonizes with the natural environment and promotes sustainability. Surveys and interviews were conducted as part of the data collection process, enabling the acquisition of valuable insights from the local community regarding their needs and preferences about a municipal market. Nature-inspired solutions were explored to optimize energy efficiency, the use of sustainable materials, and spatial arrangement. The biomimetic design serves as a driver for the harmonious coexistence between infrastructure and the natural environment in Monteverde. Furthermore, it emphasizes the significance of community involvement in the design process, promoting inclusivity and local ownership of the project......